Pemetaan Zona Potensi Penangkapan Ikan Teri Berbasis Citra Satelit dan Aktivitas Kapal Perikanan di Perairan Teluk Lampung - Mulkan Nuzapril; Dona Setya; Mestiria Harbani Sitepu (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2026)
The captured fisheries resource in Lampung Province have significant potential, particularly for anchovies. Anchovy is a small pelagic fish species commonly caught by fishermen in Lampung and holds significant economic value. This study aims to identify the spatial pattern of potential anchovy fishing zones based on satellite imagery and to integrate the spatial modeling results with information on fishing activities conducted by local fishermen. The satellite data used in this study include sea surface temperature (SST) and chlorophyll—a concentration derived from MODIS-Aqua imagery to represent environmental parameters, while vessel detection data (VBD) are used to indicate fishing activities. Data processing was conducted through spatial analysis to determine potential fishing zones based on a multi-parameter weighting approach. Validation was carried out by overlaying the modeling results with actual fishing locations obtained from fishermen. The results show that chlorophyll-a distribution ranges from 0.25 to 3.8 mg/m³, with the highest concentrations found in the northern coastal area of the bay, while sea surface temperature ranges from 28.63 to 30.86 °C. Potential anchovy fishing zones were largely identified around Pahawang Island, Pasaran Island, Sebesi Island, and the Krakatau archipelago, supported by high primary productivity and suitable temperature conditions. Interview results also indicate that fishermen consistently catch fish in these areas, with anchovies being the dominant catch throughout the year. This study confirms that satellite image analysis can provide accurate spatial information to support anchovy fishing activities in an effective, efficient, and sustainable manner.